Słowiańszczyzna w podręcznikach. Studium socjologiczne nad możliwością budowania alternatywnych narracji historycznych o początkach państwa polskiego - Kasperek, Andrzej (Studia Edukacyjne, 2017)
What has been undertaken in this study is the problem of narrations, alternative to the predominant historical discourse, about the beginning of Polish statehood. The considerations on the existence of such narrations are situated in the perspective “dominant culture – counterculture”. Some references are made to the research concerning the presentation in history course books and curricula of two events in the history of Poland: the christening of Mieszko I and the so called pagan reaction. What is suggested here is enriching the research conclusions with the issues of Romantic “revelation” and introducing Slavism into the 19th century culture as well as viewing the early state of the Piast dynasty in the Ciril-Methodius tradition. The author formulates the thesis that in the analysed coursebooks and curricula the narration about the early Polish statehood is subordinated to the evolutionaryrevolutionary model of interpreting history.